Tipping versus Cooperating to Supply a Public Good - Scott Barrett; Astrid Dannenberg (Center for Economic Studies and ifo Institute (CESifo), 2015)
In some important multi-player situations, such as efforts to supply a global public good, players can choose the game they want to play. In this paper we conduct an experimental test of the decision to choose between a tipping game, in which every player wants to contribute to the public good provided enough other players contribute, and a prisoners' dilemma, the classic cooperation game. In the prisoners' dilemma, the first best outcome is attainable, but cannot be sustained as a Nash equilibrium. In the tipping game, only a second best outcome may be attainable, but there exists a Nash equilibrium that is strictly preferred to the one in the prisoners' dilemma. We show that groups do significantly better when they choose the tipping game, and yet many groups repeatedly choose the prisoners' dilemma, indicating a mistaken and persistent tendency to prefer a game with potentially higher payoffs to one having a strategic advantage.
Keywords: C72; C92; F53; H41; 330; prisoners' dilemma; tipping game; experiment; public good; agreements; voting; environment; global public goods